2021
DOI: 10.1002/jemt.23843
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐ and microstructures of the digestive tract in the Eurasian collared dove, Streptopelia decaocto (Frivaldszky 1838): Adaptive interplay between structure and dietary niche

Abstract: We describe the functional morphology of the digestive tract of the Eurasian collared dove, Streptopelia decaocto using anatomical, morphometric, histological, histochemical, and ultrastructure techniques, and relate our findings to the species' dietary niche. Our results revealed that the esophagus is displaced on both sides of the neck and has highly folded tunica mucosa, which confer greater elasticity for efficient swallowing and passage of food to the crop. The proventriculus is delicate and its mucosal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
(167 reference statements)
4
4
0
2
Order By: Relevance
“…The folds are coated with a non-keratinized stratified squamous epithelium. These results for the macroscopic structure of the esophagus agree with those for other avian species (Ma, 2009; Sagsöz & Liman, 2009; Gelis, 2013; El-mansi et al, 2021). These authors concluded that there is a relationship between the histological structure of the esophagus and the type of nutrition and that the size of the esophageal folds is dependent on the size of the food that the birds swallow.…”
Section: Discussionsupporting
confidence: 87%
“…The folds are coated with a non-keratinized stratified squamous epithelium. These results for the macroscopic structure of the esophagus agree with those for other avian species (Ma, 2009; Sagsöz & Liman, 2009; Gelis, 2013; El-mansi et al, 2021). These authors concluded that there is a relationship between the histological structure of the esophagus and the type of nutrition and that the size of the esophageal folds is dependent on the size of the food that the birds swallow.…”
Section: Discussionsupporting
confidence: 87%
“…Our SEM observations show the presence of the two elongated choanal openings on the middle palatine portion that connect the oral cavity with the nasal cavity, similar to that described in; the Basal Tortoise (Heiss et al, 2011), the semiaquatic giant Asian pond turtle(Lintner et al, 2012) and the semiaquatic Malayan box turtle(Heiss et al, 2008). This connection between the oral and nasal cavities is also described in avian species (Abumandour, El‐Bakary, et al, 2021; Abumandour, Shukry, et al, 2021; El‐Mansi, El‐Bealy, Al‐Kahtani, et al, 2021; El‐Mansi, El‐Bealy, Rady, et al, 2021). Crocodilians, on the other hand, have a complete secondary palate that separates the oral cavity from the nasal cavity (Abramyan et al, 2014).…”
Section: Discussionmentioning
confidence: 55%
“…The Testudo kleinmanni feeds mainly on a wide diversity of the native Egyptian plants in the dry semi‐desert habitats, ranging from grasses to broadleaf plants such as perennials and herbs, which are also used as hiding places (El Din, 2006; Zwartepoorte, 2015). The oral cavity is the most adaptable structure that has adapted to different ecological conditions and is regarded as a key to understanding each animal species' lifestyle (El‐Mansi, El‐Bealy, Al‐Kahtani, et al, 2021; El‐Mansi, El‐Bealy, Rady, et al, 2021; Iwasaki, 2002). According to our research, neither the U‐shaped upper and lower valve nor the slightly serrated upper and lower lip with their numerous scale‐like projections on their surfaces have ever been described in any tortoise species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las especies exóticas representan una amenaza para la estructura, función e integridad de los ecosistemas (Ferreira et al, 2021), contribuyen a la extinción de algunas especies (Rocha et al, 2021) e introducen agentes infecciosos al ambiente colonizado (Hernandez-Colina et al, 2021). La paloma de collar turca (STRDEC, Streptopelia decaocto) es una especie invasora con amplia distribución en Norteamérica (eBird, 2021). Es un ave relativamente grande (Salazar-Borunda et al, 2019), que compite por alimento y sitios de anidación con la avifauna local (El-Mansi et al, 2021;Koenig, 2020) o bien, puede transmitir enfermedades al ambiente colonizado (Stilmmelmayr et al, 2012).…”
Section: Introductionunclassified